(untitled) (KULT_online, 2012)
The edited volume Erinnern an den Zweiten Weltkrieg (Recollect the Second World War) focuses on the different formations of national landscapes of memory in Germany, Russia, and Poland regarding WWII, with particular focus on museums and memorials. In addition to the national specifics of commemoration practices, especially common elements are addressed in order to establish a tripartite consensus on the history of the 20th century to accelerate the convergence of three formerly warring parties.